2006
DOI: 10.1111/j.1468-2982.2006.01169.x
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Spatial Neglect in a Child with Hemiplegic Migraine

Abstract: Unilateral spatial neglect (USN) is a relatively common neurological disorder observed in patients after brain injury. Patients fail to attend to the contralesional side of space (1). Although USN is well documented in adults, it has been rarely reported in children (2-10). We present a child showing USN during an attack of hemiplegic migraine, without structural brain injury. The present report is the first in which USN during migraine is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Although during aura in these patients could be present sensory, aphasic and basilar-type symptoms (2), associated with the motor involvement (1), the presence of unilateral neglect has been reported, to our knowledge, in only one case in childhood (3). We describe the first case in an adult woman with sporadic hemiplegic migraine.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Although during aura in these patients could be present sensory, aphasic and basilar-type symptoms (2), associated with the motor involvement (1), the presence of unilateral neglect has been reported, to our knowledge, in only one case in childhood (3). We describe the first case in an adult woman with sporadic hemiplegic migraine.…”
Section: Introductionmentioning
confidence: 81%
“…Enoki et al. in 2006 described a 13-year-old girl showing USN during an attack of hemiplegic migraine (3); they hypothesize that left spatial neglect may be attributed to the cortical hypoperfusion that is developed transiently on the right hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…She collided frequently with obstacles on her left side and had a positive left neglect drawing test. All symptoms disappeared in 24 h [ 46 ]. Second, a 20-year-old woman with migraine with typical visual aura since the age of 15: during one of her attacks, she presented short-lasting scintillations in the right visual field, followed by a right-sided headache (14 h duration), together with left-sided paresthesia and hemiparesis, both persisting for four hours.…”
Section: What Patients With Migraine See and Do Not Seementioning
confidence: 99%
“…Although transient neuropsychological impairment is not uncommon during a migraine attack (24), we found only one report describing brief unilateral spatial neglect during a hemiplegic migraine attack in a child revealed by administration of a neglect test and observation of drawing (25). Data collected from clinical examination, neuropsychological testing and teachers’ reports showed that our patient had a transient condition similar to NLD.…”
Section: Introductionmentioning
confidence: 99%